Gost Versus DES Encryption Algorithms - Nauom, Reyadh; Abdul-Halim, Mayada; Attea, Bara’a (Iraqi Journal of Science, 2025)
To translate text to a code is to encrypt it, and to translate it back is to decrypt it. For either operation, we need a general algorithm and a unique key. The Confidence in an algorithm grows as group after group fails to break it. The presented paper discussed two encryption algorithms; DiS. the workhorse of cryptography algorithms and GOST, their relation, and the major differences between them.